Carcass traits of Muzaffarnagari lambs under intensive and semi-intensive management systems - PAL, U K; AGNIHOTRI, M K; SINHA, N K (The Indian Journal of Animal Sciences, 2013)
Muzaffarnagari lambs (n=23) were slaughtered at 6.5 months of age to study the meat production traits under intensive and semi-intensive systems of management. Live animal and carcass measurements differed significantly (P< 0.05) between the groups. Lambs maintained under intensive system had higher (P<0.05) carcass weight and carcass yield. However. proportions of meat and bone components declined significantly (P<0.05) while the fat increased (P<O.05) substantially in the carcasses of intensively managed lambs than those in semi-intensively managed lambs. Visceral cavity fat was also significantly higher (P<0.05) in the first group. Among the non-carcass components skin, head and cannon weights were significantly higher (P<0.05) in the first group, while blood, inedibles and variety meats did not show much differences on weight basis. Per cent retail cut yield (on carcass weight basis) was almost similar in both the groups. Among the cuts.leg had highest proportion of meat and lowest proportion of fat irrespective of animal group, whereas. breast and shank cuts had lowest proportion of lean and highest proportion of bone, and rest were in between. It was concluded that intensive system was superior to semi-intensive system with respect to mutton production, however, its economics needs to be worked out in detail.